ANALISIS KESULITAN BELAJAR SISWA/I KELAS VIII MTS KAMPUNG PANJANG DALAM PROSES PEMBELAJARAN - Mariah, Kiki; Nasywaa’ri, Dinda; Ferdianti, Fadilah Maulani; Putra, Farhan Arrahman; Putri, Lufia; Nurkholifah, Nani Dwi; Putri, Riris Kumala; Sari, Tiara (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
The aim of this research is to describe and analyze various learning problems faced by class VIII students at MTs Kampung Panjang Village during their learning. Students who experience difficulty or difficulty in the learning process are called learning difficulties. Students can experience failure or be unsuccessful in achieving learning goals because of these obstacles. This study conducted descriptive research with a qualitative approach. Interviews, observations, and use of assessment instruments are the data collection methods used. This research involved all 30 students in class VIII MTs Kampung Panjang Village, who experienced learning difficulties during the learning process. This research uses a distributed evaluation of learning difficulties.